Modelo IS-PC-MR na perspectiva neokaleckiana com efeito de histerese no mercado de trabalho - Ataíde, Matheus Andrade (2025)
The main objective of this research is to develop a 3-equation which considers Investiment and Saving, Phillips Curve and Monetary Rule (IS-PC-MR) model from a Neo-Kaleckian perspective, incorporating hysteresis effects microfounded on the dynamics of class frustration in response to wage bargaining processes and the functional income distribution in the labor market and to test the hypothesis of hysteresis in Brazil’s unemployment rate. For this purpose, unit root tests, the Kalman filter, Structural Vector Autoregressions and the Generalized Method of Moments are employed, using data from the third quarter of 2002 to the first quarter of 2024. Simulations indicate that the theoretical mathematical model can be considered wage-led in terms of the demand regime and profit-led in terms of the accumulation regime. Furthermore, demand shocks impact the long-term equilibrium activity level, and the model demonstrates that, depending on the central banker’s preferences, exogenous shocks may take more or less time to dissipate, and their effects on the long-term equilibrium activity level may vary in intensity. Empirical results show evidence of a unit root in the unemployment series. Additionally, there is evidence that the NAIRU varies over time, changes with demand shocks, and responds to changes in the current unemployment rate. Evidence was found of a statistically significant relationship between variation of NAIRU and unemployment deviations from the NAIRU. Therefore, it is considered that there is statistically significant evidence that Brazilian unemployment suffers from hysteresis. Thus, the empirical results highlight that the presence of hysteresis in Brazil’s unemployment rate cannot be rejected, emphasizing the relevance of the theoretical model.